Establishment and Optimization of Molecular Cytogenetic Techniques (45S rDNA-FISH, GISH, and Fiber-FISH) in Kiwifruit (Actinidia Lindl.) - Zhao, Yang; Deng, Honghong; Chen, Yao; Li, Jihan; Chen, Silei; Li, Chunyan; Mu, Xue; Hu, Zhongrong; Li, Kunming; Wang, Weixing (Frontiers in Plant Science, 2022)
The kiwifruit (Actinidia chinensis) has long been regarded as “the king of fruits” for its nutritional importance. However, the molecular cytogenetics of kiwifruit has long been hampered because of the large number of basic chromosome (x=29), the inherent small size and highly similar morphology of metaphase chromosomes. Fluorescence in situ hybridization (FISH) is an indispensable molecular cytogenetic technique widely used in many plant species. Herein, the effects of post-hybridization washing temperature on FISH, blocking DNA concentration on genomic in situ hybridization (GISH), extraction method on nuclei isolation and the incubation time on the DNA fiber quality in kiwifruit were evaluated. The post-hybridization washing in 2×saline sodium citrate (SSC) solution for 3×5 min at 37 ˚C ensured high stringency and distinct specific FISH signals in kiwifruit somatic chromosomes. The use of 50× blocking DNA provided an efficient and reliable means of discriminating between chromosomes derived from in the hybrids of A. chinensis var. chinensis (2n=2x=58) × A. eriantha (2n=2x=58), and inferring the participation of parental genitors. The chopping method established in the present study were found to be very suitable for preparation of leaf nuclei in kiwifruit. A high-quality linear DNA fiber was achieved by an incubation of 20 min. The physical size of 45S rDNA signals was approximately 0.35-0.40 μm revealed by the highly reproducible fiber-FISH procedures established and optimized in this study. The molecular cytogenetic techniques (45S rDNA-FISH, GISH, and high-resolution fiber-FISH) for kiwifruit was for the first time established and optimized in the present study, which is the foundation for the future genomic and evolutionary studies and provides chromosomal characterization for kiwifruit breeding programs.